Evaluation of the Fitness Component of the Physical Education Curriculum for the Seventh Grade - Goudas, Μάριος; Kolovelonis, Αθανάσιος; Nikitopoulou, Χριστίνα; Hassandra, Μαρία (Inquiries in Physical Education and Sport, 2010)
The aim of the study was to examine the effectiveness of the fitness component of the physical education curriculum for the seventh grade. Participants were 37 seventh grade students from two physical education classes. Both quantitative and qualitative evaluation methods were used. Results of quantitative evaluation showed that the program had a positive effect on students’ performance in fitness tests. Qualitative results showed that students enjoyed their participation in the program, and felt that they could plan a fitness program. However, a small number of students reported negative thoughts about some aspects of the program (e.g. difficulty in tests and activities). In conclusion, the fitness component of the physical education curriculum for the seventh grade was effective, as it had a positive effect on students’ fitness performance and on their motives for participation in the program.